Relationship between tinnitus and suicidal behaviour in Korean men and women: a cross‐sectional study. (4th February 2016) - Seo, J.H.; Kang, J.M.; Hwang, S.H.; Han, K.D.; Joo, Y.H.
Abstract : Objectives: This study investigated the prevalence of suicidal ideation and behaviour in a representative sample of South Koreans with or without tinnitus. Design: A cross‐sectional study. Setting: Based on data from the 2010 to 2012 Korean National Health and Nutrition Examination Survey (KNHANES). Participants: The study included 17 446 Korean individuals. Main outcome measures: Participants provided demographic, socio‐economic and behavioural information, as well as responses to questionnaires assessing the presence and severity of tinnitus, mental health status regarding stress, depression, and suicidal ideation and attempts. In the univariate analysis, the Rao–Scott chi‐square test and logistic regression analysis were used to test the association between tinnitus and risk factors. Simple and multiple linear regression analyses were used to examine the association between tinnitus and mental status. Results: A total of 20.9% and 1.2% of participants with tinnitus, and 12.2% and 0.6% of those without, reported suicidal ideation and attempts, respectively ( P < 0.0001 and P = 0.001). Participants reporting suicide attempts showed a higher proportion of severe annoying (6.0%) and irritating (11.8%) tinnitus than those with suicidal ideation (1.4% and 10.2%, respectively). Risks for experiencing tinnitus were significantly associated with suicidal ideation and attempts after adjusting for confounding variables. Conclusion: This study has important implications for enhanced screening and evaluation of mental health status and suicidal ideation/behaviour among tinnitus patients.